Higher education and social structure in chile: approaches from three generational groups - Ghiardo, Felipe; Dávila León, Óscar (Última Década, 2020)
In the mid-2000s, evidence showed that one out of seven higher education students in Chile were the first generation in their families to reach this level of education. The present article intends to give insight into the consequences of this process for their socio-economic conditions. For that purpose, it is focused on the currently 25-30 yearold cohort, comparing the educational and labor trajectories of this first generation with higher education to two other groups: those who have higher education and are children of graduated parents (heirs) and those who are children of parents with no higher education, not even reaching that education level (reproducers). The analysis is based on the 2017 National Socio-Economic Characterization Survey (Casen), including a set of indicators about education profiles, labor activity, income and housing. Results show that, regardless of the fact that the first-generation students set apart from reproducers both in labor and social terms, a set of differences between them and the heirs mark social and labor distances.